Canine plasma and tissue fatty acid profiles and their correlation with hair coat conditions - Goh, Yong Meng; Rajion, Mohamed Ali; Mohamed Mustapha, Noordin; Teow, B. H.; Goriman Khan, Mohd Azam Khan (Veterinary Association Malaysia, 2005)
This study was initiated to study the probable relationships between the fatty acid profiles of the plasma, skin, liver and brain and to determine their correlations with hair coat conditions in owned and stray dogs. A total of35 dogs were used in this study. Twenty-three owned dogs obtained from the University Veterinary Hospital (UVH dogs) were subjected to blood sampling and hair coat scoring only. Twelve euthanized dogs were sourced from a local animal shelter (LAS dogs) and blood, brain, liver and skin samples were obtained. Hair coat scores were performed under standardized conditions and was found that the UVH dogs (median score = 4.1) had significantly better scores compared to LAS dogs (median score = 3.1, P<0.05). The UVH dogs had significantly lower (P<0.05) n-6:n-3 ratios and lower plasma arachidonate content. The skin and plasma fatty acid profiles correlated well with each other but no correlation was evident between the brain and plasma fatty acid profiles. Increased amounts of plasma and skin n-3 and n-6 polyunsaturated fatty acids were associated with better hair coat conditions. However, plasma n-6 fatty acids seemed to .have a stronger positive correlation to hair coat scores in dogs (p = 0.683, P<0.05) compared to plasma n-3 fatty acids (p = 0.512, P<0.05) and fatty acid profiles from other tissues. In summary, this report underscores the importance of n-3 and n-6 fatty acids to the hair coat condition of dogs kept under humid tropical conditions.